An Analysis of ChatGPT Response Variations to Identical Prompts Across Different Devices: A Case Study in Informatics Education - A., Hermila; Bau, Rahmat Taufik R.L; Sudirman, Randi; Siyad, Abdulaziz Ahmed (Akademi Komunitas Negeri Aceh Barat, 2025)
AbstractThe development of artificial intelligence (AI) in education has brought about various innovations, one of which is using ChatGPT as a learning tool. However, the diversity of answers provided by ChatGPT when used on different devices is still a critical question. This study aims to analyze the variation in ChatGPT's answers to the same prompt content when used on computer devices with different specifications. This research method uses an experimental approach by comparing ChatGPT output results on five types of devices with different operating systems, processors, and BIOS. The analysis is based on the level of similarity of the sentence and the meaning of the answer, with the categories “very different” (20% similarity), “different” (50% similarity), “almost the same” (70% similarity), and “same” (90% similarity). The results show a significant variation in the answers produced, with some devices giving almost identical responses while others show differences in sentence structure and information arrangement. Hardware factors, including processor type and operating system, are thought to contribute to these differences. The implications of these findings are highly relevant in the context of secondary education, where the use of ChatGPT as a learning tool is increasing. Variations in answers can lead to differences in understanding among students using devices with different specifications, thus requiring more attention from educators and AI technology developers. This study makes an important contribution in highlighting the challenges and opportunities of applying AI in education. Recommendations include standardizing the use of AI in the classroom and developing AI models that are more consistent in responding across devices. Thus, fairness and effectiveness in using AI in education can be continuously improved. AbstrakPerkembangan kecerdasan buatan (AI) dalam dunia pendidikan telah menghadirkan berbagai inovasi, salah satunya melalui pemanfaatan ChatGPT sebagai alat bantu pembelajaran. Namun, keberagaman jawaban yang diberikan oleh ChatGPT ketika digunakan pada perangkat yang berbeda masih menjadi pertanyaan kritis. Penelitian ini bertujuan untuk menganalisis variasi jawaban ChatGPT terhadap konten prompt materi yang sama ketika digunakan di perangkat komputer dengan spesifikasi berbeda. Metode penelitian ini menggunakan pendekatan eksperimental dengan membandingkan hasil keluaran ChatGPT pada lima jenis perangkat dengan perbedaan sistem operasi, prosesor, dan BIOS. Analisis dilakukan berdasarkan tingkat kesamaan kalimat dan makna jawaban, dengan kategori